PENGAPLIKASIAN METODE EARNED VALUE PADA PENGENDALIAN WAKTU TERHADAP BIAYA (Study Kasus: Proyek Penggantian Jembatan Sungai Langkolome Cs Kabupaten Muna) - Meitri Laura Bulo; Rudi Balaka; Rini Sriyani (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2013)
AbstractControl is one of the functions of project management that aims to make the jobs can run reach the target without much deviation. The concept of Value Results (eraned Value) is a control method that is used to control project costs and schedules in an integrated manner. The study